Chenodeoxycholic acid stimulated fibroblast growth factor 19 response – a potential biochemical test for bile acid diarrhoea. Issue 11 (5th April 2017) - Borup, C.; Wildt, S.; Rumessen, J. J.; Bouchelouche, P. N.; Graff, J.; Damgaard, M.; McQuitty, C.; Rainteau, D.; Munck, L. K.
Summary: Background: Bile acid diarrhoea is underdiagnosed and better diagnostic tests are needed. Fasting serum fibroblast growth factor‐19 (FGF19) has insufficient diagnostic value, but this may be improved by stimulation. Aim: To explore if an impaired FGF19 response identifies primary bile acid diarrhoea. Methods: Eight patients with primary bile acid diarrhoea and eight healthy volunteers ingested (i) a meal plus 1250 mg chenodeoxycholic acid (CDCA), (ii) 1250 mg CDCA or (iii) the meal. Blood was sampled at fasting and repeatedly after stimulation. We analysed FGF19 by enzyme‐linked immunosorbent assay and bile acids including 7α‐hydroxy‐4‐cholesten‐3‐one by liquid chromatography‐tandem mass spectrometry. Results: Stimulation with the meal plus CDCA increased median FGF19 in healthy volunteers from fasting 62 pg/mL [interquartile range (IQR): 41–138] to 99 pg/mL (IQR: 67–147; P = 0.012) after 90 min and peaked after 150 min at 313 pg/mL (IQR: 54–512). This response was impaired in primary bile acid diarrhoea patients [fasting 56 pg/mL (IQR: 42–79); 90 min: 48 pg/mL [IQR: 37–63); 150 min: 57 pg/mL (48–198)]. Receiver operating characteristics (ROCAUC ) for fasting FGF19 was 0.55 ( P = 0.75) and at 90 min 0.84 ( P = 0.02). The difference in FGF19 from fasting to 90 min after the meal plus CDCA separated the groups (ROCAUC 1.0; P = 0.001). 7α‐hydroxy‐4‐cholesten‐3‐one was elevated in primary bile acid diarrhoea ( P = 0.038) and not significantly affected by stimulation. Conclusions: The FGF19 response following chenodeoxycholic acid plus meal is impaired in primary bile acid diarrhoea. This may provide a biochemical diagnostic test. Abstract : Linked Content This article is linked to Walters paper. To view this article visithttps://doi.org/10.1111/apt.14095 .